In Silico Analysis of Glycosaminoglycan-Acemannan as a Scaffold Material on Alveolar Bone Healing - Sularsih, Sularsih; Mulawarmanti, Dian; Rahmitasari, Fitria; Siswodihardjo, Siswandono (European Journal of Dentistry, 2022)
Objective This study aimed to analyze interaction between glycosaminoglycan-acemannan as a scaffold material and toll-like receptor-2 (TLR-2) receptor, which predicted the osteogenesis potency on alveolar bone healing (in silico analysis).Materials and Methods Docking interaction between glycosaminoglycan-acemannan and TLR-2 receptor using the Molegro Virtual Docker (MVD) program. The compounds of glycosaminoglycan-acemannan and TLR-2 receptor with the structure in the form of two- and three-dimensional images were analyzed, as well as the most stable structure. It was observed the interaction of the ligand on the cavity of the TLR-2 receptor structure. The energy required for the ligand and receptor interaction (Moldock score) was calculated with MPD program.Results The chemical structure shows that glycosaminoglycan-acemannan is capable binding to the TLR-2 receptor with hydrogen bonds and strong steric interaction. The docking results were detected for five cavities where the compound binds to the TLR-2 receptor. The Moldock score of the ligand on the CAS-LYS-LEU-ARG-LYS-ILE-MSE[A] ligand was −95,58 Kcal/mol, that of acemannan was −91,96 Kcal/mol, and for glycosaminoglycan −61,14 Kcal/mol.Conclusion The compound of glycosaminoglycan-acemannan as a scaffold material is able to bind with a TLR-2 target receptor, which predicted osteogenesis activity on alveolar bone healing supported by in silico analysis.
Keywords: glycosaminoglycan; acemannan; in silico; TLR-2 receptor